Kolaborasi Pemangku Kepentingan dalam Ekowisata dan Ekonomi Kreatif Tapis Lugusari - Astriyantika , Meyliana; Cahyo, Enggar Dwi; Siregar, Damara Saputra (Jurnal Studi Perhotelan dan Pariwisata, 2025)
Purpose: The purpose of the research on the Utlization of Mocaf Flour (Modfied Casava Flour) as a Substitution Mterial fr Nastar Gluten Free Products is to innovate the manufacture of pineapple with the substitution of mocaf flour as an effort to provide the benefits of consuming cookies in a healthier way where nastar cookies with the use of mocaf flour can be enjoyed by all people from children to the elderly.Research methodology: The method used in this study is quantitative with data collection techniques including observation, interviews and distributing questionnairesResults: The purpose of this study is to prove that the factors are not analyzed but identified and indeed the 7P theory (product, place, price and promotion) is very compatible with the customer's motivation to visit Eeny Meeny Restaurant. The type of sample used is the quota sampling technique with 100 respondents, and distributed online using the Google form.Conclusions: The study found that the main reason guests visit Eeny Meeny Restaurant is the friendliness of the staff (48.9%). While menu variety, strategic location, and promotions received positive feedback, they were not the main drivers for return visits. Price was a limiting factor, as it’s less competitive and discounts are rarely offered.Limitations: This study emphasizes more on internal factors such as service, product, location, promotion, and price, without exploring in depth the influence of external factors such as culinary trends or local economic conditions.Contributions: The contribution of this research lies in a deeper understanding of the factors that influence consumer decisions in choosing a restaurant, especially at Eeny Meeny Restaurant. This study shows that service quality, especially employee friendliness, is the main factor that drives customer visits. This finding can serve as a reference for restaurant management in formulating strategies to improve service and customer experience.Keywords: Decision, Marketing mix, Motivation, Purchase, RestaurantHow to Cite: Astriyantika, M, Cahyo, E, D, Siregar, D, S. (2025). Kolaborasi Pemangku Kepentingan dalam Ekowisata dan Ekonomi Kreatif Tapis Lugusari. Jurnal studi perhotelan dan pariwisata, 3(2), 49-57.